Indian summer : musings on the gift of life - Pickering, Sam, 1941- (University of Missouri Press, 2005)
"Indian Summer is the newest collection of personal essays by Sam Pickering. In typical Pickering fashion, he seeks to capture the gift of living. He brings to the page again his family, students, and a wealth of country characters who live in places that exist only in his imagination and who wander through the stories he tells." "He describes how his life has been altered by his children leaving home for college, and he ponders the changes aging brings and the things that never change. The consummate teacher, he celebrates academic life and the pleasures of the classroom. Readers will roam familiar ground with Pickering as he explores the fields and small hills of eastern Connecticut and the bogs and woods on his farm in Nova Scotia."--Jacket